DRUG UTILIZATION IN PATIENTS WITH ACUTE POISONING: AN OBSERVATIONAL STUDY - MAWLIYA, SUBHASH; KUMAR, NARESH; PARASHAR, HARSHIT (International Journal of Current Pharmaceutical Research, 2026)
Objective: Acute poisoning is one of the major public health problems in the developing world and one of the key causes of emergency cases and deaths. Having a rational use of drugs is important in enhancing results. The objective of this study isto assess the use trends of medicines in acute poisoning individuals. Methods: It is a prospective observational study carried out in nine months (September 2024-May 2025) at a tertiary care teaching hospital in Jaipur, Rajasthan. The use of drugs was evaluated through the World Health Organization prescribing indicators. Results: 248 patients were involved. In 82.25% of the encounters, antibiotics were prescribed, and injectable drugs were prescribed in all the patients. mean of the number of drugs per encounter was 12.3. A total of 78.22 % of patients have been reported to have been cured, and the mortality rate was 5.24%. Conclusion: The paper shows that there is a high consumption of antibiotics and injectable medicines in cases of acute poisoning. The use of antimicrobial stewardship programs and regular prescription audits is needed to enhance rational drug use.